Responsible innovation in CDR: designing sustainable national Greenhouse Gas Removal policies in a fragmented and polycentric governance system - Healey, Peter; Kruger, Tim; Lezaun, Javier (Frontiers in Climate, 2024)
In the assessment of climate policies, the social sciences are sometimes assigned a restricted instrumental role, focused on understanding and mitigating social and political ‘constraints’ seen to impede the fullest achievement of a particular technological imaginary. The work represented in this paper draws on an alternative intellectual tradition, in which the technical, social and political dimensions of the problem are seen as closely intertwined, shaped by values and interests specific to each jurisdiction. The Greenhouse Gas Removal Instruments and Policies Project, (GRIP) applied this approach to the design of policies for carbon dioxide removal (CDR) in the United Kingdom. GRIP explored what policy incentives and pathways might improve the societal assessment of different CDR technologies for further development and potential deployment. Here we analyse the views of UK policy actors questioned on different CDR options, and outline policy pathways to incentivise the research and demonstration processes necessary to determine what role CDR techniques should play in climate policy. We conclude by discussing recent policy developments in the UK, and the contours of a research agenda capable of supporting a responsible evaluation of CDR options.